A comprehensive physically based approach to modeling in bioengineering and life sciences - Sacco, Riccardo; Guidoboni, Giovanna; Mauri, Aurelio Giancarlo (London : Elsevier/Academic Press, 2019)
A Comprehensive Physically Based Approach to Modeling in Bioengineering and Life Sciences provides a systematic methodology to the formulation of problems in biomedical engineering and the life sciences through the adoption of mathematical models based on physical principles, such as the conservation of mass, electric charge, momentum, and energy. It then teaches how to translate the mathematical formulation into a numerical algorithm that is implementable on a computer. The book employs computational models as synthesized tools for the investigation, quantification, verification, and comparison of different conjectures or scenarios of the behavior of a given compartment of the human body under physiological and pathological conditions. - -
Includes bibliographical references (pages 805-817) and index.
Keywords: Bioengineering -- Mathematical models; Life sciences -- Mathematical models; Mathematical models